Incidence of and risk factors for surgical site infection following canine limb amputation. Issue 3 (10th January 2022) - Billas, Alison R.; Grimes, Janet A.; Hollenbeck, Danielle L.; Dickerson, Vanna M.; Wallace, Mandy L.; Schmiedt, Chad W.
Abstract: Objective: To determine the incidence of and risk factors for surgical site infection (SSI) following canine thoracic and pelvic limb amputations. Study design: Retrospective, multicenter study. Animals: Dogs (n = 248). Methods: Medical records were reviewed for preoperative, intraoperative, and postoperative variables including indication for amputation, amputation type, method of muscle transection, duration of surgery and anesthesia, and wound classification. Follow up was ≥30 days or until SSI development. Logistic regression and Fisher's exact tests were used to compare SSI incidence to variables of interest. Results: The incidence of SSI was 12.5% for all procedures and 10.9% for clean procedures. Factors increasing odds of SSI were muscle transection with a bipolar vessel sealing device ( P  = .023 for all procedures, P  = .025 for clean procedures), procedure classified as other than clean ( P  = .003), and indication for amputation of bacterial infection ( P  = .041) or traumatic injury ( P  = .003) compared to neoplasia. Conclusion: Use of bipolar vessel sealing devices for muscle transection increased the odds of developing an SSI whereas use of electrosurgery and/or sharp transection did not. Dogs with surgical sites that were other than clean, or with bacterial infection and/or traumatic injury were also at increased odds of SSI. Clinical significance: Use of electrosurgery or sharp transection for muscle transection should be considered rather than use of bipolar vessel sealing devices to decrease odds of SSI in dogs undergoing limb amputation. Further studies across a variety of procedures are needed to validate these findings given the increasing popularity of these devices in veterinary medicine.